PELATIHAN KONVERSI SKRIPSI MENJADI ARTIKEL ILMIAH DALAM MENINGKATKAN KEMAMPUAN DAN MINAT MENULIS ARTIKEL MAHASISWA - Warka Syachbrani; Rezky Amalia Hamka; Regina (Jurnal Pemantik, 2022)
The Community Partnership Program partners are students of the Digital Business Study Program, Faculty of Economics and Digital Business, Megarezky University Makassar. The purpose of this study is to provide solutions to the problems of: (1) the lack of students ability to write scientific articles, (2) the lack of student interest in writing scientific articles (3) the obligation of students to make scientific articles as one of the requirements for completing the thesis/final assignment. The external goal is that students can make scientific articles well and structured. The methods used in this research are lectures, discussions, and training/practice. The results achieved are (1) partners have knowledge and understanding of scientific articles, (2) partners have skills to convert thesis/final project to scientific articles that well and structured.